Estudos da nutrição e da produção de substâncias que absorvem luz ultravioleta por Penicillium commune - de Carvalho, Alírio; Jardim Junior, Olympio; Lorencetti, Lilian de Lourdes; Ribeiro, Flávio Carvalho; Molinari, Rubens (Eclética Química, 1993)
.